2021
DOI: 10.3390/healthcare9091103
|View full text |Cite
|
Sign up to set email alerts
|

Related Factors and Treatment of Postoperative Delirium in Old Adult Patients: An Integrative Review

Abstract: “Postoperative delirium” is defined as delirium occurring in the hospital up to one week after a procedure or before discharge (whichever occurs first) that meets the DSM-5 diagnostic criteria. Objectives: To describe the risk factors related to this pathology and identify effective non-pharmacological forms of treatment. An integrative review of the available literature was performed. The search results considered included all quantitative studies published between 2011 and 2019 in both English and Spanish. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…As we all know, advanced age is recognised as an independent risk factor for POD. 29 What is more, a study indicated that CCI ≥2 was closely associated with POD. 13 ACCI is a wide comorbidity scoring system by integrating CCI and age, which is commonly used to predict the prognosis in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, advanced age is recognised as an independent risk factor for POD. 29 What is more, a study indicated that CCI ≥2 was closely associated with POD. 13 ACCI is a wide comorbidity scoring system by integrating CCI and age, which is commonly used to predict the prognosis in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, actions to avoid or reduce delirium incidence can be divided into three categories: preoperative, intraoperative, and postoperative strategies (Table 2) [57][58][59][60][61][62][63][64][65][66]. Due to the paucity of evidence, the actual guidelines suggest avoiding pharmacological approaches as first-line therapy both in non-intensive and intensive care settings [67][68][69].…”
Section: Perioperative Management Of Deliriummentioning
confidence: 99%
“…Currently, treatment options for POD do not appear to reduce related mortality and morbidity ( Méndez-Martínez et al, 2021 ). It is essential for clinicians to appropriately adjust perioperative care plans for primary prevention.…”
Section: Introductionmentioning
confidence: 99%